Serum Levels of Epithelial-Derived Cytokines as Interleukin-25 and Thymic Stromal Lymphopoietin after a Single Dose of Mepolizumab in Patients with Severe Non-Allergic Eosinophilic Asthma: A Short Report - Virginija Kalinauskaite-Zukauske; Andrius Januskevicius; Ieva Janulaityte; Skaidrius Miliauskas; Kestutis Malakauskas (Canadian Respiratory Journal)
The bronchial epithelium has continuous contact with environmental agents initiating and maintaining airway type 2 inflammation in asthma. However, there is a lack of data on whether reduced airway eosinophilic inflammation can affect the production of epithelial-derived mediators, such as interleukin-25 (IL-25) and thymic stromal lymphopoietin (TSLP). The aim of this study was to investigate the changes in serum levels of IL-25 and TSLP after a single dose of mepolizumab, a humanized monoclonal antibody to interleukin-5 (IL-5), in patients with severe non-allergic eosinophilic asthma (SNEA). We examined 9 SNEA patients before and four weeks after administration of 100 mg mepolizumab subcutaneously. The fractional exhaled nitric oxide (FeNO) level was analysed using an electrochemical assay (NIOX VERO®, Circassia, UK). Serum IL-25 and TSLP levels were measured by ELISA. Four weeks after the single dose of mepolizumab, blood eosinophil count significantly decreased from 0.55 ± 0.20 × 109/l to 0.14 ± 0.04 × 109/l (p=0.01) and FEV1 increased from 2.1 ± 0.5 l (65.4 ± 8.8% of predicted) to 2.6 ± 0.4 l (76.4 ± 9.1% of predicted) (p=0.04), while FeNO level has not changed (32.3 ± 8.4 vs 42.9 ± 12.6 ppb). Serum IL-25 level significantly decreased from 48.0 ± 17.2 pg/mL to 34.8 ± 17.1 pg/mL (p=0.02) with same tendency in TSLP level: from 359.8 ± 71.3 pg/mL to 275.6 ± 47.8 pg/mL (p=0.02). It has also been noticed a significant relation between changes in the blood eosinophil count and serum IL-25 level (r = 0.81, p=0.008), as well as between changes in serum IL-25 and TSLP levels (r = 0.93, p=0.004) after a single dose of mepolizumab. Thus, anti-IL-5 treatment with mepolizumab might diminish the production of bronchial epithelial-derived cytokines IL-25 and TSLP in patients with SNEA which is potentially related to reduced eosinophilic inflammation. This trial is registered in ClinicalTrial.gov with identifier NCT03388359.